ANALYSIS OF WORKING MOMS' PARENTING SKILLS IN INFLUENCED ISLAMIC EDUCATION IN EARLY CHILDHOOD IN THE DIGITAL ERA - Fathorrahman (Program Studi Manajemen Pendidikan Islam, 2026)
This study aims to analyze parenting skills (parenting skills) working mothers ( working (mom ) in instilling Islamic education in early childhood in the digital era. The development of digital technology brings new challenges to the home education process, particularly in the formation of religious values in children. Working mothers, as primary caregivers, play a strategic role in guiding and providing role models, both directly and through the use of digital media. This study used a qualitative approach with in-depth interviews with several working mothers with young children. The results show that parenting skills , including effective communication, time management, and wise use of technology, significantly influence the successful instillation of Islamic values in children. However, obstacles such as limited time and the influence of negative digital content also pose challenges. This study provides important recommendations for working mothers to improve their parenting skills and optimally utilize technology to support Islamic education at home